Formulation and investigation of Lactobacillus rhamnosus cek-R1 filled alginate microspheres with different excipients - Fehér, Pálma; Papp, Boglárka; Józsa, Liza; Sinka, Dávid; Fidrus, Eszter; Nacsa, Fruzsina; Bácskay, Ildikó; Kardos, Gábor (De Remediis, 2025)
Microspheres are spherical particles containing the active substance, in our case bacterial probiotic strain Lactobacillus rhamnosus (L. rhamnosus), in an individually coated form. L. rhamnosus is a natural constituent of the human intestinal flora and is known to improve immune function, enhance healing of the intestinal mucosa, reduce inflammation, bloating and diarrhoea. The aim of our experimental work was to formulate sodium alginate microspheres containing L. rhamnosus bacterial strain as active ingredient and prebiotic (galactooligosaccharide, pectin, inulin). The microspheres were formulated using Büchi Encapsulator equipment, after which the entrapment efficiency was measured. The lyophilized product was filled into hydroxypropylmethylcellulose (HPMC) capsules and was subjected to a dissolution assay using Erweka equipment. The number of viable L. rhamnosus was determined from samples of the dissolution fluid. The microspheres are lyophilised to improve shelf-life and facilitate filling into traditional capsules. The number of viable bacteria in the lyophilizate was determined by inoculation on medium and standard microdilution test. Microspheres containing different compositions of pro- and prebiotics were formulated, and their antioxidant capacity was detected by 2,2-diphenyl-l-1-picrylhydrazyl (DPPH). We tested the anti-inflammatory effect of the microspheres using human IL-4 ELISA Kit on colon adenocarcinoma (CaCo-2) cell line.